Sex hormone–psoriasis interactions: from sex-specific clinical features to immunoregulatory mechanisms - Dai, Yingying; Wang, Yuanting; Huang, Yuwei; Jiang, Xian; Tan, Jing (Frontiers in Immunology, 2026)
Psoriasis is a chronic inflammatory skin disease mediated by T cells, characterized by distinct sex differences and variations across different reproductive stages, suggesting that sex hormones may play a significant role in its pathogenesis. In recent years, research has increasingly focused on the bidirectional effects of sex hormones in psoriasis: on one hand, changes in hormone levels can affect the onset and progression of psoriasis; on the other hand, the systemic inflammation of psoriasis can interfere with the homeostasis of the sex hormone axis. This review systematically integrates clinical epidemiological evidence of sex hormone abnormalities in cutaneous psoriasis patients, outlines the molecular mechanisms of estrogen, androgen, and progesterone in immune-inflammatory regulation of psoriasis, and further explores how psoriasis-related inflammation, through cytokines, stress responses, and metabolic abnormalities, can in turn disrupt sex hormone balance. The focus is primarily on immunopathological mechanisms, with a secondary consideration of the impact of metabolic and stress-related factors, which modulate immune responses and may indirectly influence disease progression. We highlight the complex immune-endocrine network interaction between sex hormones and cutaneous psoriasis, emphasizing the need for future sex-stratified studies, dynamic hormone monitoring, and mechanistic validation models to clarify their causal pathways. This will aid in understanding the sex-specific clinical manifestations of psoriasis and provide a theoretical basis for developing hormone-targeted intervention strategies.